The Investigation of Occult Hepatitis B Infection in Hemodialysis, Peritoneal Dialysis, and Predialysis Patients by the Polymerase Chain Reaction Method - Dogukan, Muruvvet; Kizirgil, Ahmet; Dogukan, Ayhan (Turk Nefroloji Diyaliz Transplantasyon Dergisi, 2009)
The presence of hepatitis B virus DNA in case of negative hepatitis B surface antigen in serum is known as occult hepatitis B. Although the exact prevalance is not known, there are many reports indicating that occult hepatitis B is more frequently encountered in patients undergoing hemodialysis treatment. The aim of this study was to investigate the prevalence of occult hepatitis B in patients on hemodialysis or peritoneal dialysis, or with predialytic chronic renal failure. A total of 174 HBsAg-negative sera were included in the study. HBV-DNA was detected by polymerase chain reaction (PCR) in 2.6% of hemodialysis patients and 1.8% of peritoneal dialysis patients. In contrast, there was no occult hepatitis B virus infection in non-dialyzed patients with chronic renal failure. According to the liver enzymes and serum C-reactive protein levels, there was no statistically difference between the occult hepatitis B positive patients and the negative patients. In conclusion, although the rate was low, occult hepatitis B infections was detected among dialysis patients in our study. Therefore, despite serological analysis, both hemodialysis and peritoneal dialysis patients should be screened for occult HBV infections with a more sensitive test such as PCR, in order to prevent the dialysis-mediated transmision risk of HBV infection.
Keywords: Hemodialysis; Peritoneal dialysis; Predialysis; Occult hepatitis B; Polymerase chain reaction (PCR)